THE SAFETY NETWORK SYSTEM AND PROSPECTS FOR THE APPEARANCE OF A FINANCIAL CRISIS IN BOSNIA AND HERZEGOVINA - Plakalovic, Novo (Economic Annals, 2008)
The article is on the system of the safety network of the financial sector in Bosnia and Herzegovina (BH) and potential causes of possible financial instability. The network of protection of financial institutions in BH is to a certain extent incomplete but a high level of regulatory and supervisory activities has been present so far, which effects the expressed stability of financial institutions. Potential risks and the vulnerability of the financial system arise from a range of features which are characteristic of the local financial institutions, their activities, the condition of the BH economy, and macroeconomic stability and flows of goods and capital between the country and foreign countries. The sector of financial institutions has been privatized and it is in foreign ownership. Foreign exposure of domestic economy and financial markets is limited to only a small number of countries ( Austria , Germany ). There are pressures in respect of the increased rates of return on bank capital and there is a very high dynamic of credit growth. Possible unfavourable scenarios could bring about problems in the banking sector, which is shown by stress tests. The deterioration of the macroeconomic imbalance could also be a significant cause of serious problems in the local financial sector. There are no certain indicators that this could happen in the near future and influence the appearance of a financial crisis; however, such a situation cannot be ruled out.